2015
DOI: 10.1111/pin.12285
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillomas on core biopsy can be upgraded to malignancy on subsequent excisional biopsy regardless of the presence of atypical features

Abstract: Intraductal papillary lesions of the breast constitute a heterogeneous entity, including benign intraductal papilloma (IDP) with or without atypia and malignant papillary carcinoma. Differentiating between these diagnoses can be challenging. We re-evaluated core biopsy specimens that were diagnosed as IDP and the corresponding surgical excision specimens, and assessed the potential risk for the diagnosis to be modified to malignancy based on excision. By sorting the pathology database of the National Cancer Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 16 publications
1
48
2
2
Order By: Relevance
“…The management of papillary lesions of the breast diagnosed by CNBx has been controversial and challenging. Excision of papillary lesions with atypia or ADH/ALH has been recommended because of their high association with malignancy, but the case is not the same with the management of papillary lesions without atypia . Results have varied in the relationship between papillary lesions without atypia and cancer, with upgrade rates to a cancer diagnosis ranging from 2% to 33% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of papillary lesions of the breast diagnosed by CNBx has been controversial and challenging. Excision of papillary lesions with atypia or ADH/ALH has been recommended because of their high association with malignancy, but the case is not the same with the management of papillary lesions without atypia . Results have varied in the relationship between papillary lesions without atypia and cancer, with upgrade rates to a cancer diagnosis ranging from 2% to 33% .…”
Section: Discussionmentioning
confidence: 99%
“…Cardenosa et al also looked into the relationship of palpable abnormalities and malignancy and found that most papillary lesions are not palpable. The discrepancies in upgrade rates and clinical factors may occur for multiple reasons, including small cohort sizes, not specifically separating out IDP with atypia from those without, or just genuine differences …”
Section: Discussionmentioning
confidence: 99%
“…There is no disagreement that IDP with atypia has a high upgrade rate and high malignancy risk. However, the upgrade rate has been variably reported in IDP without atypia, and the best method to effectively treat IDP without atypia is still uncertain [167819]. Nakhlis et al [7] reported an upgrade rate of 6%, and based on this, they suggested that surgical treatment may not be necessary for IDP without atypia.…”
Section: Discussionmentioning
confidence: 99%
“…Обнаружение патологических выделений требует направления дан-ных пациентов для углубленного исследования с целью постановки диагноза и начала лечения, что способству-ет снижению объемов оперативного вмешательства и выявлению патологии на ранних стадиях. Позднее обнаружение патологических разрастаний в протоках молочных желез повышает риски внутрипротокового РМЖ и рецидивов в ранние сроки [15].…”
unclassified
“…При внутрипротоковой патологии после хирургиче-ского лечения тактика диспансерного наблюдения вклю-чает в себя физикальный осмотр молочных желез с кон-тролем выделений из соска 1 раз в 6 мес, проведением УЗИ молочных желез 1 раз в 6 мес; рекомендуется маг-нитно-резонансная томография молочных желез с кон-трастированием на сроке 2 года после оперативного вмешательства (для контроля возможного рецидивиро-вания). Данная группа пациенток требует динамическо-го наблюдения с частотой 2 раза в год на протяжении не менее 3 лет [15]. Во втором клиническом наблюдении, учитывая результаты иммуногистохимического исследования и локализованность патологического процесса, специали-зированного лечения не требовалось; частота диспан-серного осмотра составляет 1 раз в год с дополнитель-ным проведением УЗИ молочных желез.…”
unclassified